Megabenthos Assemblages and Benthic Dynamics for Sustainable Coral Reef Management in Biak, Papua - Ludi Parwadani Aji; Risandi Dwirama Putra; Ni Wayan Purnama Sari; Raden Suyadi; Ana Setyastuti (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2026)
Coral reef ecosystems are home to a diverse array of biota, including megabenthos, which serve as indicators of the present condition of these ecosystems. This research examines the occurrence and abundance of megabenthos as well as their relationship to coverage of benthic coral and turf algae in coral reef ecosystem. Sampling was conducted at 14 reef sites in Biak, Papua, Indonesia. The coverage of benthic groups and megabenthos was observed by using an underwater photographic transect and a belt transect, respectively. Coverage of coral and turf algae ranges from 5.4 to 53.7 % and from 23.9 to 68 %, respectively. The most abundance megabenthos from all locations and years was sea urchin Diadema spp., followed by Linckia laevigata, and the lowest abundance was sea cucumber. Predatory coral polyps Acanthaster planci have a lower abundance and occurrence than the other predatory coral snail, Drupella. Overall, we found a positive correlation between the abundance of Diadema spp. and Linckia laevigata and turf algae cover, and a negative correlation between the abundance of lobster Panulirus and coral cover. Human influence, such as fishing activity on economically important megabenthos groups (snail Trochidae, giant clams, lobsters, sea cucumbers), might play a role in shaping megabenthos assemblages. This research supports the sustainable management of Biak’s marine ecosystems, which provide vital ecological functions and economic resources for coastal communities.